On Meromorphic Harmonic Functions with Respect to k-Symmetric Points. (25th August 2008) - Al-Shaqsi, K.; Darus, M.
Abstract : In our previous work in this journal in 2008, we introduced the generalized derivative operator𝔇 m j forf ∈ 𝒮 ℋ . In this paper, we introduce a class of meromorphic harmonic function with respect tok -symmetric points defined by𝔇 m j . Coefficient bounds, distortion theorems, extreme points, convolution conditions, and convex combinations for the functions belonging to this class are obtained.